2022
DOI: 10.1177/15330338221116489
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemotherapy as an Alternative Treatment Option to Pelvic Exenteration for Recurrent Vulvar Cancer of the Perineum Region

Abstract: Objective: Pelvic exenteration in women with recurrent vulvar carcinoma is associated with high morbidity and mortality and substantial treatment costs. Because pelvic exenteration severely affects the quality of life and can lead to significant complications, other treatment modalities, such as electrochemotherapy, have been proposed. The aim of this study was to evaluate the feasibility and suitability of electrochemotherapy in the treatment of recurrent vulvar cancer. We aimed to analyze the treatment optio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Vivod G et al showed that electrochemotherapy might be a less radical alternative to pelvic exenteration, which is feasible and suitable for the treatment of recurrent vulvar cancer. Electrochemical therapy may be used for the treatment of locally recurrent cervical cancer [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vivod G et al showed that electrochemotherapy might be a less radical alternative to pelvic exenteration, which is feasible and suitable for the treatment of recurrent vulvar cancer. Electrochemical therapy may be used for the treatment of locally recurrent cervical cancer [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the safety and feasibility of electrochemotherapy treatment in gynecologic cancers. In the literature at present, there are only a few articles or clinical cases describing the use of electrochemotherapy in patients with vulvar or vaginal cancers for palliative purposes [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. In these articles, detailed feasibility data are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being safe and effective as a form of monotherapy, electrochemotherapy can be successfully combined with other standard treatments, such as targeted therapies (vemurafenib and dabrafenib) [ 13 ] or immunotherapy (pembrolizumab) [ 14 ]. To date, only a few articles or clinical cases have been published describing the use of electrochemotherapy in patients with vulvar cancer for palliative purposes [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. In these articles, the safety and local efficacy of electrochemotherapy have been demonstrated; however, a detailed analysis of the safety and feasibility of electrochemotherapy in vulvar cancer patients is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Safety and local efficacy after electrochemotherapy with bleomycin in locoregional cutaneous recurrences of vulvar carcinomas previously treated with chemotherapy, radiotherapy and surgery or unsuitable for standard treatments have been demonstrated. [15][16][17][18][19] The effectiveness of the clinical cases and studies is presented in Table 1. The success rate of such tumors is 80%, which is lower than the response rate of other skin tumors treated with electrochemotherapy.…”
Section: Literature Review Of Electrochemotherapymentioning
confidence: 99%